The epistemology of fake news - Flowerree, Amy K.; Grundmann, Thomas (New York, NY , United Kingdom : Oxford University Press, 2021)
"This book is the first sustained inquiry into the new epistemology of fake news. The chapters, authored by established and emerging names in the field, pursue three goals. First, to analyse the meaning and novelty of 'fake news' and related notions, such as 'conspiracy theory.' Second, to discuss the mechanics of fake news, exploring various practices that generate or promote fake news. Third, to investigate potential therapies for fake news"--
I. Analyses of Fake News. Speaking of Fake News / Romy Jaster and David Lanius -- Good News, Bad News, Fake News / Duncan Pritchard -- The Fake News about Fake News / David Coady -- Conspiracy Theories and Evidential Self-Insulation / M. Giulia Napolitano -- II. Mechanics of Fake News. Enquiry and Normative Deviance / Filippo Ferrari and Sebastiano Moruzzi -- Facing Epistemic Authorities / Thomas Grundmann -- Is Fake News Old News? / Catarina Dutilh Novaes and Jeroen de Ridder -- How Vice Can Motivate Distrust in Elites and Trust in Fake News / Maura Priest -- Echo Chambers, Fake News, and Social Epistemology / Jennifer Lackey -- The Dissemination of Scientific Fake News / Emmanuel J. Genot and Erik J. Olsson -- III. Therapies of Fake News. The Virtue of Epistemic Trustworthiness and Re-Posting on Social Media / Sarah Wright -- Fake News and Epistemic Rot; or, Why We Are All in This Together / Sanford C. Goldberg -- An Epistemic Defense of News Abstinence / Sven Bernecker -- Fake News, False Beliefs, and the Fallible Art of Knowledge Maintenance / Axel Gelfert -- Trust No One? / Michael Baurmann and Daniel Cohnitz
Includes bibliographical references and index.
Keywords: Fake news -- Philosophy; Applied philosophy; Informational works; Informational works